The Classical Athens before the “Age of Pericles”: the Lost Monuments of Architecture and Painting - Nalimova, Nadezhda A. (Actual Problems of Theory and History of Art, 2012)
The so called «Age of Pericles» is considered to be the time of the highest flourishing of the Athenian classical art. However, not less bright epoch is represented by the decades that preceded the political leadership of Pericles (470–460 BC), when classical Athens was going through its fi rst rise of art and construction activity. This article covers the obscure and lost works of monumental art of this period known only through literary sources and archaeological evidence.